Grade repetition and indiscipline: evidence from Brazil and Portugal in Pisa, 2012 - Matos, Daniel Abud Seabra (2016)
The main objective of this paper is to analyze grade repetition in Brazil and Portugal, using data from the Programme for International Student Assessment – PISA –, 2012, by applying a multilevel logistic regression model with repetition as the dependent variable in order to identify characteristics of students and schools that are associated with the probability of repetition and thus estimate the variability among schools. The most significant contribution of this work is the explication of a clear association between grade repetition and lack of scholastic discipline. Further studies, based on longitudinal data, are needed to investigate in detail the characteristics of students and schools that are associated with the changes in educational conditions which influence the probability of grade repetition.